PENGARUH EFEKTIVITAS DEWAN KOMISARIS DAN KOMITE AUDIT, STRUKTUR KEPEMILIKAN, DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Eka Lestari; Murtanto Murtanto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
The purpose of this study was to examine, analyze, and find empirical evidence of the influence the effectiveness of the board of commissioners and audit committee, concentrated ownership, managerial ownership, institutional ownership, and audit quality on earnings management with company size, company performance, and leverage as variable controls. The sample used in this study was 42 companies listed on the Indonesia Stock Exchange (IDX) in period 2013-2015. The sampling technique used was purposive sampling. This study used multiple regression analysis. The results of this study show that effectiveness of the board of commissioners, concentrated ownership, managerial ownership have negative effect on earnings management. However, the effectiveness of audit committees, institutional ownership, and audit quality doesn’t have effect on earnings management. As well, the firm size, firm performance, and leverage have effect on earnings management.